Rabindranath: Inner Vision of Art and Literature: Exploring the Influence of Art and Literature in the Life of Rabindranath Tagore (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present article centers particularly around the job and noteworthiness of the arts and literature in the life of Rabindranath Tagore. He characterized literature as that which is unified with life, and he trusted that no one but which can give us genuine freedom. It is along these lines fundamental that during the time spent literature we accomplish the inside and out advancement of the person for amicable change in accordance with reality. The arts ought to be a basic part of life and of literature, as it is just through the arts that it is conceivable to express one's involvement and acknowledgment of the amicable association between the universe, the individual reality and immortality, notwithstanding their being a wellspring of joy. Just the arts (and nature as an educator) empower the improvement of the whole identity, and additionally the view of reality and truth. Tagore along these lines comprehends the job of the arts in the life of the person as a key factor in the development of hisher identity, adding to humankind. In this paper we examine about the effect of art and literature in Rabindranath Tagore's life.